The Variations of the Concept of Justice: An Analysis - Wuraola, Oluwabusayo Temitope (NIU Journal of Humanities, 2018)
The idea of the concept of justice varies from man to man, family to family, locality to locality, state to state, country to country and even continent to continent. The inquiry about justice goes from the crudest to the most refined interpretation of it. The basis of justice can be traced to conscience and morals. Philosophers have different theories of justice. This contributes to the assertion that a definite meaning of justice is hard to come by. Some see it as a shield to the weaker people in the society; others envision a society of equal citizens with equal rights. The ‘rights of citizens’ is one of the basic features of justice. In claiming these rights by citizens, arguments build up as to unjust actions. An example is the nature of secularism in Turkey, the ban placed on the hijab and the violation of the right to freedom of religion of women. Also, an intimate look at current issues in the world brings one to the conclusion that it is not possible for everyone to be just; just like everyone cannot be equal. Pertinently, there are different angles to justice. We have economic justice, political justice, social and Islamic justice. People ascribe justice to the least of their interactions in the society. This paper seeks to examine, through the use of primary and secondary materials, the concept of justice by looking into the foundation of justice and the theories of justice by different philosophers; to dissect the concept of justice into different aspects; and analyse some of the current issues on justice. Keywords: Justice, Natural justice, Fairness, Ethics, Equality, Constitution, Right to Privacy